THE ROLE OF FINANCIAL AND OPERATIONAL INDICATORS IN PREDICTING THE NON-CONTINUITY OF THE ECONOMIC UNIT / AN APPLIED STUDY IN A SAMPLE OF IRAQI COMMERCIAL BANKS - Forat Sattar Hassoon; Naeem Sabah khilkhal; Iraq Hayder Oudah Kadhim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The research aims to identify the financial and operational indicators to predict the failure of the economic unit during the coming period, and to identify the obstacles that face the external auditor during the review process, especially with regard to this forecasting process. The research hypotheses were formulated to find the relationship between financial and operational indicators and the prediction of the continuity of the economic unit. The research sample is represented by a group of administrators, accountants, auditors and financial analysts in a sample of Iraqi commercial banks for the financial year data ending on 12/31/2020. A questionnaire was designed to be consistent with the research objectives and hypotheses, and a set of statistical methods were used. Finally, a set of conclusions were reached, the most important of which was that the financial and operational ratios and indicators have a role in measuring and evaluating the profitability and liquidity of the project and the extent of its efficiency and financial leverage, and thus both financial and operational indicators can help in predicting the lack of continuity of the economic unit.